Financial Sector Assessment : Republic of Latvia - World Bank (Washington, DC, 2013)
Latvia has a well-developed financial sector, but in the aftermath of the 2008-09 global financial crisis, access to finance has become a major constraint for the development of private enterprises. Credit to the private sector in Latvia, at above 100 percent of Gross Domestic Product, or GDP, is one of the highest in Eastern Europe, after significant growth over the last decade. However, in the aftermath of the 2008-09 financial crisis, credit growth has been negative (average annual growth of -7 percent between FY2009-2011) and access to finance has become one of the most significant obstacles for growth according to enterprises (close to 30 percent of firms identify it as an obstacle in 2009, versus 2 percent before the crisis). This contributed to a significant decline in the volume of private investment, which dropped by 48 percent between 2008 and 2010. Credit constraints are more severe in specific segments, including smaller firms. In response to these challenges, the Government has supported credit to the private sector through various instruments, some of which may need to be reviewed. Support has been provided through various financial instruments aimed at enhancing the accessibility and affordability of credit and implemented trough public bodies and commercial financial intermediaries. It will also be important to ensure the programs create adequate incentives for financial intermediaries to expand services to underserved markets in a sustainable manner, and that the programs lever the established capacity and expertise of robust commercial lenders, minimizing competition with such lenders.